Electro-chemo-mechanical effect in Gd-doped ceria thin films with a controlled orientation. Issue 28 (13th July 2020) - Santucci, Simone; Zhang, Haiwu; Sanna, Simone; Pryds, Nini; Esposito, Vincenzo
Abstract : Enhanced Gd-doped ceria electrostriction: This study uncovers new anisotropic properties in thin films, enhancing the effect along with the 〈100〉 directions by one order of magnitude and proposing a new microscopic model to explain such findings. Abstract : Gd-doped ceria (CGO) fluorite exhibits prominent electro-chemo-mechanical properties and giant-electrostriction at room temperature and has been recently disclosed in both CGO polycrystalline films and bulk. The electromechanical properties of CGO depend on the oxygen vacancy defects of the fluorite lattice. Early experiments suggest that defects along the [111] crystallographic direction promote high atomic distortion. These factors result in the largest electrostriction response ever measured. However, only out-of-plane electrostriction ( i.e. M 13 ) in (111) CGO oriented thin films has been reported so far, and several questions remain open about the electrostriction mechanism in the oxygen-defective fluorite. Here, we present electromechanical performances along different crystallographic directions. We grow thin films by pulsed laser deposition on single crystal substrates to obtain longitudinal and shear deformations ( i.e. M 11 and M 12 ) of highly coherent (100), (110) and (111) oriented CGO thin films. As a result, we find an order of magnitude higher electrostriction coefficient along [100]. Such an analysis gives a new insight into the mechanism of CGO electrostriction.